Analysis of deposits formed during biomass co-firing on 15Mo3 under different gas and temperature conditions. (January 2015) - Lay, V. F.; Higginson, R. L.; Hogg, S. C.; Kirk, C. A.; Davis, C.
Abstract : This paper reports on the analysis of fly ash and oxides on 15Mo3 after the co-firing of eucalyptus and a Russian coal at various temperatures and gas conditions for 50 hours. The loose deposits present have been characterised using X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). Results show that under reducing conditions KCl deposition is increased and a variation in oxide scale composition is observed. Complex silicates, often present as spheres are imaged through SEM.